111k views
4 votes
12. x2 - 4x - 6 = x2 + 4x – 2

User Soramimo
by
5.9k points

1 Answer

3 votes

Answer:

  • The required value of x is - 1/2.

Explanation:

We have to find the value of x from the given equation.

  • x² - 4x - 6 = x² + 4x – 2

Step: Add the like terms.

  • x² - 6 +2 = x² + 4x + 4x

Step: Add the unlike terms.

  • x² - 6 + 2 = x² + 4x + 4x
  • x² - 4 = x² + 8x

Step: Arrange in simplest form.

  • x² - 4 = x² + 8x
  • x² - x² = 8x + 4
  • 0 = 8x + 4
  • - 4 = 8x
  • 8x = - 4
  • x = - 4/8
  • x = -½

Therefore, the required value of x is - 1/2.

User Rossanna
by
5.7k points